2013
DOI: 10.4028/www.scientific.net/amm.319.444
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Piercing Process of Large-Sized Seamless Steel Tube

Abstract: In the piercing process of the large-sized seamless steel tube, the rollers and plug affected on the billet with extrusion and friction. It made that the stress and strain state of metal is very complicated. In the complex state, the casting shrinkage and void produced by molten steel solidification became the crack defect in the middle of tube wall. The simulation of the piercing process of large sized seamless steel tube was performed by FEM in this paper. The material is stainless steel TP321. The distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In many of the reviewed scientific contributions, the constitutive model is not described. On the other hand, in some of them, it is only specified if a rigid-plastic, rigid-viscoplastic, elasto-plastic or elasto-viscoplastic approach is considered [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In addition, other authors claim that they have used the material constitutive model from the FE software database without giving details about the specific formulation used, or only state that the flow stress was dependent on the temperature and the strain rate [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In many of the reviewed scientific contributions, the constitutive model is not described. On the other hand, in some of them, it is only specified if a rigid-plastic, rigid-viscoplastic, elasto-plastic or elasto-viscoplastic approach is considered [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In addition, other authors claim that they have used the material constitutive model from the FE software database without giving details about the specific formulation used, or only state that the flow stress was dependent on the temperature and the strain rate [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7]. More details and recent studies about the cross-roll piercing process can be found in Refs.…”
mentioning
confidence: 99%